Agriculture is a panacea in all emergencies - Rizal, Govinda; Karki, Shanta; Dahal, Kishor (Applied Science and Technology Annals, 2020)
Agriculture is a panacea during all emergencies except the emergencies in agriculture itself. The recent novel coronavirus that caused COVID-19 pandemic has once again rejuvenated this realization. In Nepal, where the agrarian economy is still predominant, the effect of the pandemic differs from that of industrialized and developed countries where commercial agriculture is in practice. The fear of the outbreak of COVID-19, lockdown for its prevention, and diversion of state resources to health and other welfare sector have both direct, and indirect as well as short-term, mid-term, and long-term effects on the agriculture sector. Until now there is no complete assessment of the loss caused by the lockdown in the agriculture sector. Therefore, this study was conducted to collect representative data and information regarding the loss caused at different stages of various agricultural commodities. The data were collected using a semi-structured questionnaire survey from 60 respondents and analyzed using MS-Excel. The findings show that the harvest and supply chain of perishable vegetables, fruits, fish, poultry, dairy, and cut-flower sectors were the worst hit during the lockdown in Nepal. Many city-dwellers returned to villages during lockdown time that coincided with rice cultivation season. The rice harvests later in the year is expected to be high and enough for the country. However, the challenges are the timely availability of inputs, uncertainties of weather, limitation of storages, and disturbances in the internal distribution system. These challenges should be converted into an opportunity to develop the overall agricultural sector through utilization of the currently available surplus human resource for increase in quality production, establishing agri-processing industries, smoothening of the marketing and distribution channels.